Frequency of HER-2 NEU Receptor Positivity and its Relationship with Estrogen Progesterone Receptors in Patients of Breast CA - Fahad Abbas, Amir Usman, Tahir Hamid, Javeria Usman, Mansab Ali, Javed Rafique Malik, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Carcinoma breast is the commonest malignancy of females all over the world and second leading cause of death due to cancer among females. In Pakistan it is more common at a young age contrary to the West where it is more common in old age (after 60 years). The objectives of this cross sectional study were to determine the frequency of HER-2/neu receptor over-expression and its association with some of the features of breast cancer like patient age, ER/PR status, tumour size, histological grade and axillary lymph node involvement. Methods: This study was conducted at Surgery ward unit 2, Fatima Memorial Hospital, Lahore, from June 2015 December 2015. Study included all patients with breast cancer admitted in Surgery unit 2 of FMH, Lahore for Modified Radical Mastectomy (MRM). The resected specimens were sent to histopathologist for immunohistochemical (IHC) studies (HER-2/neu receptor and ER/PR) and detailed histopathological analysis including tumour subtype, size, histological grade and involvement of axillary lymph nodes. Patients refusing HER-2/neu receptor immunohistochemistry were excluded from the study. Name, age, sex, other relevant data, detailed history and clinical examination findings and results of investigation were recorded. Data was analyzed with SPSS version 10. Results: This study included 50 patients of breast cancer having modified radical mastectomy (MRM). Age distribution ranged from 45-61 years with a Mean±SD of age 52.2±4.3 years. 30 out of 50 patients (62.5%) were >52 years, while 20 patients out of 50 (40%) were ≤40 years of age. The HER-2/neu receptor status was found positive in 30 patients (60%) and negative in 20 patients (40%) of the total cases While, it was significantly associated with tumour size (p<0.05) and negative ER/PR status (p<0.05). Conclusion: Due to high prognostic significance and frequency in Pakistani females with breast cancer, HER-2/neu receptor should be checked in all patients with breast cancer so that the positive cases should have herceptin therapy and benefit from anthracycline based chemotherapeutic agents which can improve survival in these patients.